The Overall Proficiency in English Composition of Indonesian University Students of EFL - Bambang Yudi Cahyono (TEFLIN, 2000)
Abstract: This study was aimed at examining the students overall proÃÂficiency in English composition across university-year cohorts and across academic options. The participants were undergraduate students of UniÃÂversitas Negeri Malang. They were asked to write persuasive essays on whether violence as exposed on TV programs should be restricted. The essays were evaluated using the ESL Composition Profile. The results showed that that there was a significant difference between the first- and fourth-year students overall proficiency in English composition. In adÃÂdition, there was no significant difference between the overall proficiency in English composition of the students taking the thesis option and those taking non-thesis option. The instructional program and writing curricuÃÂlum appeared to play an important role in developing the students over-all proficiency in English composition. However, the thesis prerequisite courses provided to prepare the students to write a thesis proposal did not seem to affect their overall proficiency in English composition.